Gender-UseIT. HCI, Usability und UX unter Gendergesichtspunkten (2014)
Systematic interdisciplinary research on usability that takes gender into account is still in its infancy. These conference proceedings document the first German language symposium devoted to this theme. The papers include examples from research and practice, recommendations for gender-sensitive software design, and theoretically grounded approaches for reflecting on gender in the usability engineering process and in HCI research.